Paraneoplastic Phenomena of Disseminated Intravascular Coagulopathy in Hepatic Angiosarcoma – Rare, Challenging and Fatal. Case Report and Literature Review - Strainienė, Sandra; Jauniškis, Kipras; Savlan, Ilona; Pamedys, Justinas; Stundienė, Ieva; Liakina, Valentina; Valantinas, Jonas (Acta medica Lituanica, 2021)
Background. Hepatic angiosarcoma is an uncommon, malignant, primary liver tumor, comprising 2% of liver cancers and accounting for < 1% of all sarcomas. Patients usually present with nonspecific symptoms, such as fatigue, weight loss, right upper quadrant pain, anemia, which leads to late diagnosis of an advanced stage tumor. The median life expectancy after the diagnosis of hepatic angiosarcoma is about 6 months, with only 3% of patients surviving more than 2 years. Liver failure and hemoperitoneum are the leading causes of death in patients with liver angiosarcoma. In rarer cases, it might cause paraneoplastic syndromes such as disseminated intravascular coagulopathy. The treatment of angiosarcomas is complicated as there are no established and effective treatment guidelines due to the tumor’s low frequency and aggressive nature. Case summary. We present the case of a 68-year old woman who was admitted to the hospital due to fatigue and severe anemia (hemoglobin 65 g/l). Laboratory results also revealed high-grade thrombocytopenia (8 × 109/l). The abdominal ultrasound and computed tomography scan showed multiple lesions throughout with hepatic angiosarcoma. The treatment with first-line chemotherapy (doxorubicin) was initiated despite ongoing paraneoplastic syndrome – disseminative intravascular coagulopathy. However, the disease was terminal, and the patient died 2 months since diagnosed. Conclusions. Hepatic angiosarcoma is a rare and terminal tumor. Therefore, knowledge about its manifestations and effective treatment methods is lacking. Disseminative intravascular coagulopathy is a unique clinical characteristic of angiosarcoma seen in a subset of patients.